Protective role of butyrate in obesity and diabetes: New insights - Mayorga-Ramos, Arianna; Barba-Ostria, Carlos; Simancas-Racines, Daniel; Guamán, Linda P. (Frontiers in Nutrition, 2022)
Studies in human microbiota dysbiosis have shown that short-chain fatty acids (SCFAs), propionate, acetate, and particularly butyrate, positively affect energy homeostasis, behavior, and inflammation. This positive effect can be demonstrated in the reduction of butyrate-producing bacteria observed in the gut microbiota of individuals with type 2 diabetes (T2DM) and other energy-associated metabolic alterations. Butyrate is the major end product of dietary fiber bacterial fermentation in the large intestine and serves as the primary energy source for colonocytes. In addition, plays a key role in reducing glycemia and improving body weight control and insulin sensitivity. The major mechanisms involved in butyrate regulation include key signaling pathways such as AMPK, p38, HDAC inhibition, and cAMP production/signaling. Treatment strategies using butyrate aim to increase its intestine levels, bioavailability, and improvement in delivery either through direct supplementation or by increasing dietary fiber in the diet which ultimately generates a higher production of butyrate in the gut. In the final part of this review, we present a summary of the most relevant studies currently being carried out in humans.